A Culture-Centered Approach to Experiences of the Coronavirus Pandemic Lockdown Among Internal Migrants in India. (September 2021) - Mookerjee, Devalina; Chakravarty, Sujoy; Roy, Shubhabrata; Tagat, Anirudh; Mukherjee, Shagata
India's coronavirus lockdown forced low-wage migrant workers to return from the city to the home towns and villages from which they came. Pre-pandemic living and working conditions were already stressful and difficult for these migrants. The lockdown became an additional burden, since it shut down sources of income with no assurance about when, or if, work and earning to support families could be resumed. This article draws on the lens of the Culture-Centered Approach (CCA) to understand how workers engaged with and navigated these difficult times. A total of 54 migrant workers locked-down at home across the Indian states of Bihar, Uttar Pradesh, and West Bengal were interviewed for this qualitative study. Financial worries were found to be endemic, with rising debt a major source of stress, and educational qualifications becoming an obstacle to earning. Returning migrants were suspected of bringing the virus from the city, and so stigmatized in their home towns and villages. However, the pandemic lockdown also showed some unexpected healthful consequences. It provided these marginalized, and always busy workers the time and space to stop working for a while, to stay home, eat home food, and take walks in the comparatively green and clean spaces of their home environments. In this, the pandemic lockdown may be seen to have enabled a measure of agency and health in the lives of these workers, an oasis albeit temporary, and ultimately subject to the demands of the globalized cities of India.